Challenge and Yield of Enrolling Racially and Ethnically Diverse Patient Populations in Low Event Rate Clinical Trials. Issue 1 (January 2018) - Sheffet, Alice J.; Howard, George; Sam, Albert; Jamil, Zafar; Weaver, Fred; Chiu, David; Voeks, Jenifer H.; Howard, Virginia J.; Hughes, Susan E.; Flaxman, Linda; Longbottom, Mary E.; Brott, Thomas G.
Abstract : Background and Purpose—: We report patient enrollment and retention by race and ethnicity in the CREST (Carotid Revascularization Endarterectomy Versus Stent Trial) and assess potential effect modification by race/ethnicity. In addition, we discuss the challenge of detecting differences in study outcomes when subgroups are small and the event rate is low. Methods—: We compared 2502 patients by race, ethnicity, baseline characteristics, and primary outcome (any periprocedural stroke, death, or myocardial infarction and subsequent ipsilateral stroke up to 10 years). Results—: Two hundred forty (9.7%) patients were minority by race (6.1%) or ethnicity (3.6%); 109 patients (4.4%) were black, 32 (1.3%) Asian, 2332 (93.4%) white, 11 (0.4%) other, and 18 (0.7%) unknown. Ninety (3.6%) were Hispanic, 2377 (95%) non-Hispanic, and 35 (1.4%) unknown. The rate of the primary end point for all patients was 10.9%±0.9% at 10 years and did not differ by race or ethnicity ( P inter >0.24). Conclusions—: The proportion of minorities recruited to CREST was below their representation in the general population, and retention of minority patients was lower than for whites. Primary outcomes did not differ by race or ethnicity. However, in CREST (like other studies), the lack of evidence of a racial/ethnic difference in the treatment effect should be interpreted with caution because of low statistical power to detect such a difference. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00004732.